Courses
Courses for Kids
Free study material
Offline Centres
More
Last updated date: 29th Nov 2023
Total views: 381.9k
Views today: 4.81k

# Without actually calculating the cubes , find the value of the following: $-\left( {{\left( -12 \right)}^{3}}+{{\left( 7 \right)}^{3}}+{{\left( 5 \right)}^{3}} \right)$ .

Verified
381.9k+ views
Hint: The given problem is related to algebraic identities. $-\left( {{\left( -12 \right)}^{3}}+{{\left( 7 \right)}^{3}}+{{\left( 5 \right)}^{3}} \right)$ is of the form ${{a}^{3}}+{{b}^{3}}+{{c}^{3}}$ and here $a+b+c=0$. So, the identity ${{a}^{3}}+{{b}^{3}}+{{c}^{3}}-3abc=0$, when $a+b+c=0$, is applicable here.

Let’s consider three numbers $a,b$ and $c$, such that $a+b+c=0$. We have to find the value of ${{a}^{3}}+{{b}^{3}}+{{c}^{3}}$.
We know ${{\left( a+b+c \right)}^{2}}={{a}^{2}}+{{b}^{2}}+{{c}^{2}}+2\left( ab+bc+ca \right)$. We can write ${{\left( a+b+c \right)}^{3}}$ as ${{\left( a+b+c \right)}^{2}}\left( a+b+c \right)$.
So, ${{\left( a+b+c \right)}^{3}}=\left( a+b+c \right)\left( {{a}^{2}}+{{b}^{2}}+{{c}^{2}}+2\left( ab+bc+ca \right) \right)$ .
On multiplying the terms in the right-hand side of the equation, we get:
${{\left( a+b+c \right)}^{3}}={{a}^{3}}+{{b}^{3}}+{{c}^{3}}+{{a}^{2}}\left( b+c \right)+{{b}^{2}}\left( c+a \right)+{{c}^{2}}\left( b+a \right)+2\left( ab+bc+ca \right)\left( a+b+c \right)$
$\Rightarrow {{\left( a+b+c \right)}^{3}}={{a}^{3}}+{{b}^{3}}+{{c}^{3}}+3{{a}^{2}}(b+c)+3{{b}^{2}}(a+c)+3{{c}^{2}}(a+b)+6abc$
Shifting ${{a}^{3}}+{{b}^{3}}+{{c}^{3}}$ to left-hand side of the equation and rest of the terms to right-hand side of the equation, we get:
${{a}^{3}}+{{b}^{3}}+{{c}^{3}}={{\left( a+b+c \right)}^{3}}-3{{a}^{2}}(b+c)-3{{b}^{2}}(a+c)-3{{c}^{2}}(a+b)-6abc$
Now, we will subtract $3abc$ from both sides of the equation. So, we get:
$\Rightarrow {{a}^{3}}+{{b}^{3}}+{{c}^{3}}-3abc={{\left( a+b+c \right)}^{3}}-\left[ 3{{a}^{2}}(b+c)+3{{b}^{2}}(a+c)+3{{c}^{2}}(a+b)+9abc \right]$
$\Rightarrow {{a}^{3}}+{{b}^{3}}+{{c}^{3}}-3abc={{\left( a+b+c \right)}^{3}}-\left[ 3{{a}^{2}}b+3{{a}^{2}}c+3abc+3{{b}^{2}}a+3{{b}^{2}}c+3abc+3{{c}^{2}}a+3{{c}^{2}}b+3abc \right]$
Now, on rearranging the terms, we get:
${{a}^{3}}+{{b}^{3}}+{{c}^{3}}-3abc={{\left( a+b+c \right)}^{3}}-\left[ 3{{a}^{2}}b+3{{b}^{2}}a+3abc+3{{b}^{2}}c+3{{c}^{2}}b+3abc+3{{c}^{2}}a+3{{a}^{2}}c+3abc \right]$
Now, taking $3ab,3bc$ and $3ca$ common, and substituting ${{\left( a+b+c \right)}^{3}}=\left( a+b+c \right)\left( {{a}^{2}}+{{b}^{2}}+{{c}^{2}}+2\left( ab+bc+ca \right) \right)$ , we get:
${{a}^{3}}+{{b}^{3}}+{{c}^{3}}-3abc=\left( a+b+c \right)\left( {{a}^{2}}+{{b}^{2}}+{{c}^{2}}+2\left( ab+bc+ca \right) \right)-\left[ 3ab\left( a+b+c \right)+3bc\left( a+b+c \right)+3ca\left( a+b+c \right) \right]$
Taking $\left( a+b+c \right)$ common, we get
${{a}^{3}}+{{b}^{3}}+{{c}^{3}}-3abc=\left( a+b+c \right)\left( {{a}^{2}}+{{b}^{2}}+{{c}^{2}}-ab-bc-ca \right)......(i)$
Now, when $(a+b+c)=0$ , equation $(i)$ becomes ${{a}^{3}}+{{b}^{3}}+{{c}^{3}}-3abc=0$.
Now, we will consider the given problem. We are asked to find the value of $-\left( {{\left( -12 \right)}^{3}}+{{\left( 7 \right)}^{3}}+{{\left( 5 \right)}^{3}} \right)$ without actually calculating the cubes. Comparing ${{\left( -12 \right)}^{3}}+{{\left( 7 \right)}^{3}}+{{\left( 5 \right)}^{3}}$ with ${{a}^{3}}+{{b}^{3}}+{{c}^{3}}$, we get $a=-12,b=7$ and $c=5$. On calculating the value of $(a+b+c)$ , we can see $a+b+c=-12+7+5=0$. As $a+b+c=0$ , so, ${{a}^{3}}+{{b}^{3}}+{{c}^{3}}-3abc=0$.
Or, $-\left( {{a}^{3}}+{{b}^{3}}+{{c}^{3}} \right)=-3abc$.
So, $-\left( {{\left( -12 \right)}^{3}}+{{\left( 7 \right)}^{3}}+{{\left( 5 \right)}^{3}} \right)=-3\times \left( -12 \right)\times 7\times 5=1260$.
Hence, the value of $-\left( {{\left( -12 \right)}^{3}}+{{\left( 7 \right)}^{3}}+{{\left( 5 \right)}^{3}} \right)$ is equal to $1260$.

Note: Most of the students remember the formula ${{a}^{3}}+{{b}^{3}}+{{c}^{3}}-3abc=0$, but do not remember the condition for the formula to be true, i.e. $(a+b+c)=0$ which can be very dangerous. So, instead of remembering ${{a}^{3}}+{{b}^{3}}+{{c}^{3}}-3abc=0$, it is better to remember the complete formula ${{a}^{3}}+{{b}^{3}}+{{c}^{3}}-3abc=\left( a+b+c \right)\left( {{a}^{2}}+{{b}^{2}}+{{c}^{2}}-ab-bc-ca \right)$. It is true for any condition and thus, the student will be on a safe side and can use this formula in any condition.